Pharmacokinetic Properties of Single and Multiple Doses of Ertugliflozin, a Selective Inhibitor of SGLT2, in Healthy Chinese Subjects. Issue 1 (1st April 2019) - Li, Yinhua; Mu, Yuting; Shi, Haihong; Liang, Yali; Liu, Zeyuan; Matschke, Kyle; Hickman, Anne; Krishna, Rajesh; Sahasrabudhe, Vaishali
Abstract: Ertugliflozin, a sodium‐glucose cotransporter 2 inhibitor for the treatment of type 2 diabetes mellitus, prevents renal glucose reabsorption resulting in urinary glucose excretion. This open‐label, parallel cohort, randomized study conducted in healthy Chinese adults residing in China assessed the pharmacokinetics, tolerability, and safety of 5 mg and 15 mg of ertugliflozin following single (fasted condition) and multiple‐dose (fed condition) administration. Sixteen subjects were randomized and completed the study. Ertugliflozin absorption was rapid, with maximum plasma concentrations observed 1 hour after dosing under fasted conditions and 2 to 4 hours after dosing under fed conditions. Following single‐ and multiple‐dose administration, ertugliflozin exhibited dose‐proportional exposures with an apparent mean terminal half‐life of approximately 9.5 to 11.9 hours. Steady state was reached after 4 once‐daily doses. The accumulation ratio based on the area under the plasma concentration–time curve after multiple‐dose administration was approximately 1.3 and 1.2 for ertugliflozin 5 mg and 15 mg, respectively. Ertugliflozin was generally well tolerated following administration of single and multiple oral doses of 5 mg and 15 mg in healthy Chinese subjects. Pharmacokinetic comparison with non‐Asian subjects indicated that there are no clinically meaningful racial differences and no dose modification of ertugliflozin is required based on race or body weight.